Connexin 43 Is a Potential Prognostic Biomarker for Ewing Sarcoma/Primitive Neuroectodermal Tumor. (8th May 2011) - Bui, Marilyn M.; Han, Gang; Acs, Geza; Reed, Damon; Gonzalez, Ricardo J.; Pasha, T. L.; Zhang, Paul J.
Abstract : Connexins (Cxs) are building unit proteins of gap junctions (GJs) that are prognostic markers in carcinomas. To investigate the role of Cx in Ewing sarcoma (EWS)/primitive neuroectodermal tumor (PNET), we examined the expression of Cx43 and Cx26 in 36 EWS/PNETs and found (1) cytoplasmic Cx43 reactivity in 28/36 (78%) cases. (2) Cx43 score was significantly correlated with overall survival (P = .025 ). The average scores for patients alive and dead at 3 years are 46.08 and 96.98 (P = .004 ) at 5 years are 46.06 and 96.42 (P = .002 ). (3) Metastasis had a significant effect on the overall survival (P = .003 ). (4) Cytoplasmic Cx26 reactivity was detected in 2 of 36 (6%) patients who died with metastasis. Our results suggest a possible oncogenic and prognostic role for Cx43 and Cx26 in EWS/PNET. The lack of membranous immunoreactivity suggests that the effect of Cx in EWS/PNET is via a GJ function-independent mechanism.